2023
DOI: 10.20492/aeahtd.1231180
|View full text |Cite
|
Sign up to set email alerts
|

Böbrek Bi̇yopsi̇ Vakalarimizin Anali̇zi̇: Tek Merkez Deneyi̇mi̇

Abstract: Amaç: Böbrek biyopsisi, renal parankimal hastalıkların tanısal değerlendirmesinde altın standarttır. Bir nefrolog ya da girişimsel radyolog tarafından ultrasonografi eşliğinde perkütan olarak uygulanmaktadır. Bu çalışmamızda böbrek biyopsi yapılan hastaların demografik özellikleri, biyopsi endikasyonları, biyopsi sonrası gelişen komplikasyonları, biyopsi işleminin yeterliliği, tanıları ve patolojik özelliklerini inceleyerek, hastalarımızın takip ve klinik özellikleri hakkında yol gösterici fikirler elde etmeyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…In our study, the most common chronic systemic diseases in patients who underwent kidney biopsy were found to be HT (83.3%), DM (24.3%), CAD (22.7%) and CKD (21.2%). Studies have reported that HT is the most common chronic disease in elderly patients who underwent biopsy, with rates ranging from 24.1% to 78% [20][21][22][23][24] . The rate of DM was reported to be 15.3% by Ozturk et al 20 and 29.4% by Tuğcu et al 23 , similar to that in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the most common chronic systemic diseases in patients who underwent kidney biopsy were found to be HT (83.3%), DM (24.3%), CAD (22.7%) and CKD (21.2%). Studies have reported that HT is the most common chronic disease in elderly patients who underwent biopsy, with rates ranging from 24.1% to 78% [20][21][22][23][24] . The rate of DM was reported to be 15.3% by Ozturk et al 20 and 29.4% by Tuğcu et al 23 , similar to that in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that HT is the most common chronic disease in elderly patients who underwent biopsy, with rates ranging from 24.1% to 78% [20][21][22][23][24] . The rate of DM was reported to be 15.3% by Ozturk et al 20 and 29.4% by Tuğcu et al 23 , similar to that in our study. As renal reserves decrease with aging, additional diseases that may cause kidney disease, especially DM, atherosclerotic vascular diseases and HT, facilitate the development of new kidney pathologies.…”
Section: Discussionmentioning
confidence: 99%